Implikasi Ontologi Filsafat Pendidikan Islam terhadap Pemahaman Hakikat Manusia dalam Kurikulum SMP Muhammadiyah 8 Surakarta - Irsyad Mahardi Hanardika; Mujiburrohman Mujiburrohman (TSAQOFAH, 2026)
An understanding of the nature of human beings is a fundamental aspect of Islamic educational philosophy because it determines the direction, objectives, and orientation of the educational curriculum. This study aims to explore the implications of the ontology of Islamic educational philosophy for understanding the nature of human beings in the curriculum of SMP Muhammadiyah 8 Surakarta, particularly in character formation and the development of students’ potential. This study employed a qualitative descriptive approach with a field study design. Data were collected through interviews, observation, and documentation, and were then analyzed descriptively and interpretatively to identify the ontological values underlying the curriculum and educational practices at the school. The findings show that the understanding of human beings as spiritual, social, and potential beings is reflected in the curriculum structure, learning strategies, and character development approaches at SMP Muhammadiyah 8 Surakarta. These findings affirm that the school curriculum contains an ontological foundation that views students as subjects of education who are directed to develop toward insan kamil. The conclusion of this study indicates that the ontology of Islamic educational philosophy plays an important role in developing a curriculum that is integral, humanistic, and oriented toward the holistic development of human potential. The implications of this study provide a theoretical contribution to the development of Islamic educational philosophy and a practical reference for Islamic educational institutions in designing a basic education curriculum that is more aligned with the concept of human nature in Islam.